Scripture and epic: a comparativist looks at the biography of the Buddha - Allen, N (Visva-Bharati, 2000)
The Buddha's life-story has been told in many forms, but the earliest sources (in Pali and Chinese) were made available in French by Andre Bareau in 1963. Using Bareau, I study the story in the light of Indo-European cultural comparativism. The Founder's experiences between leaving home and making his early converts are compared with those of Odysseus as he travels from Circe's home to Nausicaa's. Two trifunctional comparativist analyses by Georges Dumezil are set within a pentadic framework. Despite their differences, the two stories are sufficiently similar to suggest that much of the scriptural narrative derives from early Indo-European epic.